Idiopathic thrombocytopenic purpura treatment in a relapsed/refractory multiple myeloma patient after chimeric antigen receptor T cell therapy - Lei Qiu (Regenerative Therapy, 2020)
The adoptive transfer of CAR-T cells, which are modified T cells expressing chimeric antigen receptors (CARs), to target B cell maturation antigen (BCMA) has demonstrated impressive results in treating relapsed/refractory multiple myeloma. Although BCMA CAR-T therapy induces certain complications in some patients, idiopathic thrombocytopenic purpura (ITP) has not been reported as one of them. To the best of our knowledge, this is the first report of the successful treatment of ITP that arose in a relapsed/refractory multiple myeloma patient following anti-BCMA CAR-T cell infusion. Herein, we describe this relatively uncommon complication and provide guidance on its treatment.